Zeuxine grandis Seidenf. (Orchidaceae) - an Addition to the Orchid Flora of India - Avishek Bhattacharjee (Taiwania, 2010)
Zeuxine grandis Seidenf., is being reported for the first time from India. We provide line drawing and color photo of specimen of Z. grandis in support of our treatment and to facilitate identification of the species.